STRATEGIC JUDGMENT OF THE ACCOUNTANT (Economic journal of Lesya Ukrainka Volyn National University, 2022)
Today's business requires timely management decisions. Accurate and clear presentation of information is required to obtain data that will serve as a basis for their implementation. The executor of this link are accountants, who by virtue of their moral, professional and professional beliefs must, in their own judgment, make important decisions that will have the final coverage in the financial results of the enterprise. Achieving the required level of competitive strategy of the enterprise, economic security of the enterprise requires constant monitoring, control, assessment and analysis of risks that affect the activities and development on this basis of measures to eliminate them, the executors of which are accountants. That is why it is necessary to explore the essence of professional judgment of the accountant in the context of strategic management accounting in modern domestic practice.To manage and control the development of the enterprise in the interests of its owners and other interested partner groups (creditors, customers, suppliers, staff, society, etc.) requires quality and timely information about the business activities of the entity. The aim of the article is to highlight the role of professional judgment of an accountant as a key player in processing and presenting important data for impartial decisions.Therefore, this article explores modern approaches to understanding the professional judgment of the accountant, studied its content and role in the accounting process. That allows to formulate the need for an important solution to everyday problems of the enterprise, making the right decisions interprets the proper attitude to the moral opinion of the accountant, based on facts, practice and professional opinion, which form «real accounting» - the appropriate result, appropriate, reliable, understandable basis in making management decisions to prevent the impact of threats on the enterprise. The corresponding result requires the need for further research in the context of professional judgment in the areas of management accounting and institutional theory.
Keywords: strategic management, strategic plan, accounting thinking, managerial staff